Comparative quality assessment of edible and blended edible oils - Ratnesh Kumar,; Suresh Chandra,; Samsher,; Vikrant Kumar,; Balwant Singh,; Vipul Chaudhary, (Journal of Oilseed Brassica, 2026)
The chemical and physical properties of oils are amongst the most important properties that determine the quality andhelp to describe the present condition of oils. The soybean oil used as based oil for replacement. The soybean oil wasreplaced by (40-85); mustard, sunflower and groundnut are each (5-20%). pH of individual and blended oil was rangedbetween 3.2 to 5.4, density (0.892 to 0.900), Specific gravity (0.8363 to 0.8391), Free fatty acid (0.14 to 0.19), Iodine value(2.20 to 2.22), Peroxide value (0.16 to 0.34), pH, density, Sp. gravity, Iodine value, FFA, Peroxide value of individual as wellas blended oil was increased with increase the storage period under different storage condition. This affects was seenas replacement of soybean oil from other oil i.e. sunflower, groundnut and mustard oil. The storage oils at roomtemperature affect the quality of oil during storage.